2020
DOI: 10.1088/1361-665x/ab85a7
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory alloy reinforced vitrimer composite for healing wide-opened cracks

Abstract: A new 3D printable vitrimer based self-healing composite was fabricated and investigated in this study. In this new system, the vitrimer, which was designed and synthesized in our previous study, was used as the matrix of the composites. Tensile programed shape memory alloy (SMA) wires, with a concentration of 0.34% by volume, were used to serve as the crack closing device and provide a certain reinforcement to the composites. Polycaprolactone-diol (PCL-diol) was used as the external healing agent for the wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Vitrimers with dynamic covalent bonds based on associate mechanisms are able to maintain crosslinked networks when heat is applied [68] and are consequently able to build controlled multishape memory vitrimer by hot-pressing [67], as Pei and colleagues reported. With optimized synthesis methods to further investigate, such as introducing 3D-printable composites [66], controlling the tensile strength property by adjusting the molar ratio of crosslinking functional groups [69], improving the mechanical properties and shape fixity Another essential emerging class of SMPs is vitrimers, or covalent adaptable networks (CANs). Such thermosetting polymers are biobased, solvent-resistant and recyclable, thus offering various functionalities in industrial applications, such as protective coatings, reinforced or adhesive composite materials and biomedical devices [66,67].…”
Section: Shape-memory Intelligent Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitrimers with dynamic covalent bonds based on associate mechanisms are able to maintain crosslinked networks when heat is applied [68] and are consequently able to build controlled multishape memory vitrimer by hot-pressing [67], as Pei and colleagues reported. With optimized synthesis methods to further investigate, such as introducing 3D-printable composites [66], controlling the tensile strength property by adjusting the molar ratio of crosslinking functional groups [69], improving the mechanical properties and shape fixity Another essential emerging class of SMPs is vitrimers, or covalent adaptable networks (CANs). Such thermosetting polymers are biobased, solvent-resistant and recyclable, thus offering various functionalities in industrial applications, such as protective coatings, reinforced or adhesive composite materials and biomedical devices [66,67].…”
Section: Shape-memory Intelligent Polymersmentioning
confidence: 99%
“…With optimized synthesis methods to further investigate, such as introducing 3D-printable composites [66], controlling the tensile strength property by adjusting the molar ratio of crosslinking functional groups [69], improving the mechanical properties and shape fixity Another essential emerging class of SMPs is vitrimers, or covalent adaptable networks (CANs). Such thermosetting polymers are biobased, solvent-resistant and recyclable, thus offering various functionalities in industrial applications, such as protective coatings, reinforced or adhesive composite materials and biomedical devices [66,67]. Vitrimers with dynamic covalent bonds based on associate mechanisms are able to maintain crosslinked networks when heat is applied [68] and are consequently able to build controlled multishape memory vitrimer by hot-pressing [67], as Pei and colleagues reported.…”
Section: Shape-memory Intelligent Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, it is found that both the recovery strain and recovery stress of the tension‐programmed SMP fibers play a key role in closing cracks 20 . In particular, a certain recovery stress is needed to overcome the constraint by materials surrounding the crack or even by external tensile load in order to bring the fractured surfaces in contact 12,16,21 . While shape memory polymers usually have large recovery strain, their recovery stress is limited 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The crack healing mechanism is in two stages: bringing the fractured surfaces together, followed by healing of the surfaces in contact through physical/chemical means, which is called close‐then‐heal (CTH) 4,5 . One approach is to embed tension‐programmed shape memory fibers into the polymer matrix as a crack‐closing suture, such as shape memory alloy (SMA) wires or shape memory polymer (SMP) fibers, or even polymeric artificial muscles 6–18 . Finite element analyses have shown that the small recovery strain of SMA wires limits their ability to close cracks.…”
Section: Introductionmentioning
confidence: 99%